1985/86ネン カキ ナンキョクカイ インドヨウク ニオケル ヒョウメン カイスイチュウ ノ クロロフィル α リョウ ノ レンゾク カンソク - 谷村, 篤; タニムラ, アツシ; 服部, 寛; ハットリ, ヒロシ; 福地, 光男; フクチ, ミツオ; Tanimura, Atsushi; Hattori, Hiroshi; Fukuchi, Mitsuo (1996)
P(論文) 新たに製作した表面海水モニタリングシステムを用いて, 1985/86年夏季「しらせ」航路に沿った表面海水中の植物プランクトンクロロフィルa濃度および海洋環境パラメター(水温, 塩分, 溶存酸素および栄養塩濃度)の連続観測を実施した。南極海インド洋区の三つの海洋前線(亜熱帯収束線, 亜南極前線および南極前線)を横切る南北方向のクロロフィルa濃度の変化は海洋環境パラメターの変化と良い対応がみられた。また, オングル海峡の定着氷上の定点でのクロロフィルa量の経時的な変化は, 栄養塩濃度の変化と負の相関が見られた。 Temporal and spatial variations of phytoplankton chlorophyll a concentration together with the variations of oceanographic parameters (temperature, conductivity, dissolved oxygen and nutrient salt concentrations) were studied with an automated data acquisition system, which was newly designed and installed on board the Japanese icebreaker SHIRASE. Variations of chlorophyll a concentration across three oceanic frontal zones (Subtropical Convergence, Subantarctic Front and Polar Front) in the Indian sector of the Antarctic Ocean showed positive and/or negative correlations with the oceanographic parameters. Temporal variations of chlorophyll a concentration at a fixed point in coastal fast ice area in the Ongul Strait showed a negative correlation with nutrient salts. departmental bulletin paper